Properties of harmonic functions which are starlike of complex order with repect to symmetric points - Aini Janteng; Suzeini Abdul Halim (Hikari Ltd, 2009)
Let H denote the class of functions f which are harmonic, orientation preserving and univalent in the open unit disc D = {z : |z| < 1}. This paper defines and investigates a family of complex-valued harmonic functions that are orientation preserving and univalent in D and are related to the functions starlike of complex order with respect to symmetric points. The authors obtain extreme points, convolution and convex combination properties.